The Relationship Between Parenting and Educational Environment on the Aggressive Behavior Of Street Children In The Emas Indonesia Foundation, Medan City - Hanina, Hanina (Kirana Publisher (KNPub), 2022)
This study aims to determine the relationship between parenting and the educational environment on the aggressive behavior of street children at Yayasan Emas Indonesia Medan. This type of research is associative research. The data collection in this study was carried out through a survey approach with a quantitative descriptive type of research by distributing questionnaires to 30 respondents, while the population used in this study were street children who were recorded at the Golden Indonesia Foundation, Medan City, aged under 17 years. Data collection techniques were carried out by interviews, questionnaires and documentation studies. The data analysis tool used in this study uses SPSS (Statistical Product Software Solution). The data analysis techniques in this study were descriptive analysis, multiple linear regression analysis, hypothesis testing using a partial significant test (t test), simultaneous significant testing (F test), and testing the coefficient of determination (R2). The results of this study indicate that there is a relationship between parenting and the educational environment on the aggressive behavior of street children at Yayasan Emas Indonesia.